Students’ Involvement in School and Parental Support: Contributions to the Socio-Educational Intervention - Felizardo, Sara (2016)
Student involvement in the school and the perception of parental support are core variables in the context of studies on personal and school adjustment of children and adolescents and should be considered in the context of socio-educational intervention. In this study, we formulated the following objectives: i) to understand the differences in students’ involvement in school and the perception of parental support, according to several socio- demographic and school variables, ii) to analyse the relationship between involvement and the perception of parental support iii) to outline socio-educational intervention strategies in the contexts of children’s lives. This is a non-experimental, correlational and cross-sectional study by means of a non-probabilistic convenience sample consisting of 150 children, aged between 10 and 16 years, attending the 2nd and 3rd cycles basic education [5th – 9th years of schooling] attending a school in the central region of Portugal. The data collection instruments were “Students’ Engagement in School: a Four-Dimensional Scale – SES-4DS” (Veiga 2013, 2016), the “Perceived Parental Support Scale” (Veiga, 2011) and a part with socio-demographic and school questions was added. We found significant differences in overall (and partial) amounts of student involvement and the perception of parental support, depending on the age, gender (in agency and behaviour subscales), school difficulties/retentions and methods of study (time, a place to study and a study schedule). We also found positive and significant relationships between student involvement and perception of parental support. The results are in line with the scientific literature in the field, which highlights the key role of the variables, student involvement and perception of parental support in the academic and psychosocial adjustment of young people. These should be considered in the context of socio-educational intervention. Given the above, we present areas and action strategies promoting parent and student involvement in the educational process.